Efektivitas Terapi Murottal dan Birthing Ball Terhadap Penurunan Nyeri Kontraksi Pada Ibu Bersalin Kala I Fase Aktif - Omega DR Tahun; Ilmi Muslihat (Universitas Pahlawan Tuanku Tambusai, 2025)
Childbirth provides an unpleasant outlook for women due to pain of around 85 – 95%. Only 10 – 15% of births do not experience excessive labor pain. Every woman has a different perception of pain so the intensity of the pain felt is also different. Labor pain in mothers giving birth can be minimized by providing labor pain management measures. Labor pain management is divided into two, namely pharmacological and non-pharmacological. Non-pharmacological management of labor pain is done naturally, without the use of drugs. One method that is gaining popularity is murotal therapy, which involves the use of soothing voice recordings of verses from the Koran. On the other hand, using a Birthing Ball, this ball can help mothers relieve muscle tension and increase blood circulation, thus potentially reducing pain during contractions. This study aims to identify the effectiveness of murottal and birthing ball therapy in reducing contraction pain in mothers giving birth during the first active phase at TPMB Ika Lustiani. This type of research is pre-experimental analytical descriptive research with pretest posttest non-equivalent group design with hypothesis testing using the Wilcoxon approach. Data collection was carried out from November 2024 to January 2025. The sampling technique was total sampling, namely all mothers giving birth at TPMB Ika Lustiani. Data collection uses observation sheet instruments. The results of this study showed differences in contractions during the first active phase before and after Murottal and Birthing Ball Therapy with a significance value of 0.000 (<0.05).